A Review of Recent Advances and Future Directions in the Management of Salinity Stress in Finger Millet - Mbinda, Wilton; Mukami, Asunta (Frontiers in Plant Science, 2021)
Salinity stress is a major environmental impediment for the crop growth and production. Finger millet [Eleusine coracana (L.) Gaertn.] is an important cereal that is grown in arid and semi-arid areas of the world characterized by erratic rainfall and scarce good quality water. Finger millet salinity stress is caused by accumulation of soluble salts due to irrigation without proper drainage system, coupled with underlying rocks with high salt content which leads to salinization of arable land. This problem is projected to aggravate further due to climate change. The use of new and efficient strategies that provide stable salinity tolerance across a wide range of environment, guarantees future sustainable production of finger millet. In this review, we analyze the strategies that have been used for salinity stress management in finger millet and discuss potential future directions towards development of salt-tolerant finger millet varieties. This review also includes the example of how advanced biotechnological tools has been used in developing salt-tolerant plants. The biotechnological techniques discussed in this review are simple to implement, have design flexibility, low cost and highly efficient. This information provides an insight for accelerating the finger millet salinity tolerance and production improvement.